The Effects of Filler Loading on Mechanical Properties of Coir and Bagasse Reinforced Polyethylene Biocomposites - Lanai Wan, Alvin (Universiti Teknologi Petronas, 2010)
The aim of the study is to investigate the effect of filler loading on the mechanical properties of coir and bagasse reinforced high density polyethylene (HDPE). Particulate size fibres were treated with 3 wt% of vinyltriethoxysilane to improve the adhesion between the fillers and HDPE. The fillers and matrix were compounded at filler loading of 0, 5, 10 and 15 wt% fillers using injection moulding machine to produce dog bone shapes for testing. Tensile strength of the biocomposites was observed to decrease as natural fillers were incorporated. No significant changes in tensile strength for both biocomposites were observed when filler loading was increased. Filler loading had no effect on the flexural strength of coir biocomposite as well. However, the flexural strength for bagasse biocomposite decreased gradually as filler content was increased. Scanning electron microscope micrographs at fracture surface revealed fibre pullouts, filler agglomeration, and debonding due to poor matrix/fibre adhesion